New combinations in Hyacinthaceae subfam. Ornithogaloideae - Martínez-Azorín, Mario; Dold, Anthony P.; Crespo, Manuel B.; Alonso-Vargas, María Á. (Phytotaxa, 2021)
Within the framework of a taxonomic revision of Hyacinthaceae subfamily Ornithogaloideae, we present two new combinations in Eliokarmos for South African species, and five new combinations in Loncomelos for taxa occurring in Iran and Iraq. Details on the concerned types are given, and a new lectotype is designated.